Predictors for early cardiac death after discharge from successfully treated acute myocardial infarction - Choi, Young; Lee, Kwan Yong; Kim, Sang Hyun; Kim, Kyung An; Hwang, Byung-Hee; Choo, Eun Ho; Lim, Sungmin; Kim, Chan Jun; Kim, Jin-Jin; Byeon, Jaeho; Oh, Gyu Chul; Jeon, Doo Soo; et al. (Frontiers in Medicine, 2023)
Background: The use of a cardioverter defibrillator for the primary prevention of sudden cardiac death is not recommended within 40 days after acute myocardial infarction (AMI). We investigated the predictors for early cardiac death among patients who were admitted for AMI and successfully discharged. Methods: Consecutive patients with AMI were enrolled in a multicenter prospective registry. Among 10,719 patients with AMI, 554 patients with in-hospital death and 62 patients with early non-cardiac death were excluded. Early cardiac death was defined as a cardiac death within 90 days after index AMI. Results: Early cardiac death after discharge occurred in 168/10103 (1.7%) patients. Defibrillator was not implanted in all patients with early cardiac death. Killip class ≥3, chronic kidney disease stage ≥4, severe anemia, cardiopulmonary support usage, and left ventricular ejection fraction (LVEF) ≤35% were independent predictors for early cardiac death. The incidence of early cardiac death according to the number of factors added to LVEF criteria in each patient was 2.8% for 0 factor, 6.5% for 1 factor, and 9.9% for ≥2 factors. Each model that sequentially added the factors in the presence of LVEF criteria showed a significant gradual increase in predictive accuracy and an improvement in reclassification capability. A model with all factors showed C-index 0.729 [95% CI 0.69–0.769]; p < 0.001, IDI 0.004 [95% CI 0–0.008]; p < 0.001, and NRI 0.35 [95% CI 0.222–0.478]; p < 0.001. Conclusions: We identified 5 predictors for early cardiac death after discharge from AMI. These predictors would help to discriminate high-risk patients over current LVEF criteria and to provide an individualized therapeutic approach in the subacute stage of AMI.